Impact of psychological capital on organizational citizenship behavior: Mediation by work engagement. Issue 7 (14th August 2017) - Gupta, Manish; Shaheen, Musarrat; Reddy, Prathap K.
Abstract : Purpose: The purpose of this paper is to examine the mediating role of work engagement (WE) between psychological capital (PsyCap) and the two facets of organizational citizenship behavior (OCB) which involves both individual and organization. It also examines the moderating role of perceived organizational support (POS) between PsyCap and WE, and WE and the two facets of OCB. Design/methodology/approach: A total of 293 responses gathered from employees working in diverse service sector industries in India were assessed using structural equation modeling. Findings: Overall, the results support the mediating role of WE in the PsyCap-OCB relationship, and the moderation of POS between WE and the two facets of OCB. Research limitations/implications: This study helps in understanding how WE-OCB relationship can be negatively affected in the presence of high POS. Practical implications: The results encourage organizations to establish systems for enhancing the engagement levels of their employees, which according to this study may be achieved by creating and maintaining vibrant work environment. Originality/value: This study helps in understanding the role of POS among PsyCap, WE, the two factors of OCB.